Effect of age on lung adaptation to high-altitude hypoxia in Tibetan sheep - Zhao, Pengfei; Li, Shaobin; Zhao, Fangfang; Hu, Jiang; Wang, Jiqing; Liu, Xiu; Zhao, Zhidong; Li, Mingna; Luo, Yuzhu (Frontiers in Veterinary Science, 2024)
After prolonged adaptation to high-altitude environments, Tibetan sheep have developed a robust capacity to withstand hypobaric hypoxia. Compared to low-altitude sheep, various organs and tissues in Tibetan sheep have undergone significant adaptive remodeling, particularly in the lungs. However, whether lambs and adult Tibetan sheep exhibit similar adaptations to high-altitude hypoxia remains unclear. In this study, we selected six lambs (4 months old) and six adult (3 years old) female Tibetan sheep to assess their blood gas indicators, observe lung microstructures, and measure the expression levels of key proteins in the lungs. The results indicated that adult sheep exhibited higher hemoglobin concentrations and finer, denser pulmonary vasculature, which enhanced their oxygen-carrying capacity and increased the surface area available for blood gas exchange, resulting in improved oxygen transfer capacity. Conversely, lambs demonstrated larger lungs relative to their body weight and greater pulmonary vascular volumes, which increased relative pulmonary ventilation and blood flow, thereby enhancing oxygen uptake. These findings suggested that Tibetan sheep employ different adaptation strategies to high-altitude hypoxia at various life stages.